Factors associated with alcohol, tobacco and illicit drug use among Brazilian undergraduate students - Mayla Paula Torres Simplício; Leonardo Barbosa e Silva; Leidjaira Lopes Juvanho; Silvia Eloiza Priore; Sylvia do Carmo Castro Franceschini (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the factors associated with the use of alcohol, tobacco and illicit drugs among Brazilian undergraduate students. Methods: observational, cross-sectional study, with convenience sampling, conducted in 2014/2015, involving institutional data and a self-completed online questionnaire, analyzed using measures of frequency, central tendency/dispersion and logistic regression. Results: among 126,326 students, 62.8% reported alcohol use; 11%, tobacco; and 7.5%, illicit drugs. Several academic factors-such as not residing with family (sororities [alcohol: aOR:2.38;95%CI:2.28-2.48; tobacco: AOR:2.20;95%CI:2.09-2.33; illicit drugs: AOR:2.53;95%CI:2.38-2.70]), acting in university movements (student [alcohol: AOR:1.74;95%CI:1.65-1.83; tobacco: AOR:1.97;95%CI:1.86-2.08; illicit drugs: AOR:2.43;95%CI:2.28-2.59] and religious [alcohol: AOR:0.28;95%CI:0.26-0.29; tobacco: AOR:0.23;95%CI:0.21-0.26; illicit drugs: AOR:0.18;95%CI:0.16-0.21]) and lack of discipline/study habit (alcohol: AOR:1.41;95%CI:1.37-1.45; tobacco: AOR:1.53;95%CI:1.46-1.59; illicit drugs: AOR:1.85;95%CI:1.76-1.94) - were associated with the use of the three categories of substances. Conclusions: we identified that a number of academic factors are associated with licit and illicit drug use. These findings may help in designing preventive strategies among college students.